O direito à educação escolar do adolescente autor de ato infracional no município de Belo Horizonte/MG - Danilo Medeiros de Santana Collado (2013)
The present study focuses on the adolescent offender from the perspective of the right to education. This person is recognized by Brazilian law as having rights according to the doctrine of integral protection, priority of public policy and demand Government educational measures with the purpose of ensuring their training as citizens. The current legal jurisdictions of Brazil, the Federal Constitution, the Child and Adolescent Statute, the Law of Directives and Bases of Education and the National Socio-Educational System, predict a legal warranty rights ruled by the articulation of sectorial policies, in which education participate as a fundamental right to developing of children and adolescents in Brazil. The relevance of research is the investigation of the relevant factors to the realization of the right to education, analyzing the legal provision of acting school in the service network as well as the perception of the actors involved in the city of Belo Horizonte. With this research, we intend to reflect on the social function of education in the context of under socio forward to the challenge of universal provision, the promotion of equality and respect for difference. The research shows that the attendance policy, guided by confidentiality about the knowledge of adolescents enrolled and the infraction committed, limits the possibilities for action in the process of school care.